Understanding ureteropelvic junction obstruction: how far have we come? - Costigan, Caoimhe S.; Rosenblum, Norman D. (Frontiers in Urology, 2023)
Congenital anomalies of the urinary tract are a major cause of chronic kidney disease in both adults and children. Ureteropelvic junction obstruction, usually detected as urinary tract dilatation in utero, is one of the most common forms of CAKUT. As antenatal ultrasound technology advances and screening becomes more widespread, increasing numbers of infants with this UPJO will be detected. Management of these infants presents a clinical conundrum, as distinguishing mild benign cases from those who may develop severe renal impairment is challenging. Herein we propose that an understanding of normal developmental and pathological mechanisms involved in UPJO is important in the armamentarium for tackling this challenging condition.